Efektivitas Penggunaan Lembar Kerja Peserta Didik (LKPD) Berbasis Model Project Based Learning Berbantuan Aplikasi Tracker dengan Pendekatan Saintifik pada Materi Gerak Harmonis Sederhana - ana, Lusi (Jurnal Penelitian Pembelajaran Fisika, 2020)
This research is motivated by the demands of the 2013 curriculum which states that the 2013 curriculum was developed based on the challenges of advancing information technology, the rise of creative and cultural industries, and the development of education at the international level. Then, an innovation is needed in the form of developing learning models, learning resources and learning media that are in line with the demands of the 2013 curriculum, including LKPD as a simple learning resource that is easily understood by students, project based learning learning model as one of the recommended learning models in Curriculum 2013 and can improve the competence and creativity of students, and tracker applications as IT-based learning media that can compete at the level of international education. The purpose of this study is to produce project-based learning based learning LKPD with tracker application with scientific approach on Simple Harmonious Motion material with effective criteria. The LKPD that was developed was effective in improving students' competencies including knowledge competencies (84.13), attitude competencies (82.55), and skills competencies (83.48). The results of the study can be concluded that the LKPD developed is effective in improving the competence of students and can be applied to a broader scope.